The U.S. tax program for Swiss banks: What determined the penalties? - Yvan Lengwiler; Albana Saljihaj (University of Basel, Center of Business and Economics (WWZ), 2018)
The U.S. Tax Program for Swiss Banks is a very significant part of the recent history of the Swiss financial industry. It has accelerated the transformation of the Swiss banking industry from a system that relied on bank secrecy to a much more compliant one. It was also rather costly for the banks involved. This short paper tries to identify the determinants of the individual penalties that were levied by the DoJ.
Keywords: G21; H26; 330; tax evasion; bank secrecy